Sieving Effect of Sorting Machine with Vibration Table Type on Cacao Pod Based Compost - Siswoyo Soekarno; Edy Suharyanto; Ahmad Hudi Arif (Jurnal Keteknikan Pertanian, 2009)
Cacao pod is the biggest part (70% of weight) of Cacao, which was not optimaly utilized.Cacao podis one of organic material that can be functioned as an organic fertilizer, such as compost. When utilizedwith right proportion, organic fertilizer is safe for plants and not degrades the soil composition. Compostingprocess is one of utilization form of Cacao pod. The size reduction of cacao pod in the organic fertilizerprocess would help to accelerate the composting process. Smaller particle size would faster interacting withenvironment, so the composting process would be well accelerated if compared to the material with biggersize. Chopping machine of Cacao pod is used to cut the biomass to be small particle in order to be able tobe utilized as some important necessity, i.e. fertilizer or farm animals feed. However, Varies compost sizewas one of the problems faced in the composting process. Therefore, the sorting process was needed tobe done after chopping process, so the compost size became uniform and fulfill the user demand. Thisresearch was aimed at knowing the slope effect of sorting machine and rotation speed (RPM). The methodused in analyzing the results of this research was comparing the treatment factors, which are shown withhistogram. As the super small size of compost recommended for applying in the fertilizing process, so theoptimum treatment combination for having high mass fraction of SS compost grade was achieved at 12oslope of sieve table and 1400 RPM motor rotation speed. As bigger the particle densities of the compostsize as smaller the compost porosity. Mass loss was very low at all treatment combination with the valuearound 0.43-1.33%, so the sieving efficiency can be said very high.Keywords : vibration table type, slope of sieve table, motor speed rotation (RPM)Diterima: 24 Maret 2009; Disetujui: 16 September 2009